Optimization of Bilateral Cooperation at the Local Level: Vocational Schooling Program and Firm Productivity in Central Java - Wiryawan, Bangkit A.; Herawati, Nunik Retno; Rum, Muhammad; Perkasa, Ricardo Gita (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
In 2011 the Indonesian and the German government initiated the Sustainable Economic Development through Technical and Vocational Education and Training Program (SED-TVET). Within the diplomacy realm, this kind of bilateral strategy has often been utilized to strengthen a country's specific needs. Following the program, Provincial Government in Central Java responds distinctively to the initiative by emphasizing link and match program to promote skilled-labor employment. This paper aims to investigate the effect of these national and local policies on firms’ productivity. Our identification of treatment year is critical as this precedes wider implementation of TVET program at the national level in 2016. To capture the precise treatment effect of the program, we deploy difference-in-difference strategy using the province’s neighbors as the control group. We find that firms in Central Java employed nearly 20% higher share of skilled labor relative to its controls. This correlates with significantly higher productivity and export performance. The results highlight the benefit of well-coordinated bilateral cooperation while also stressing the important role of local leadership in optimizing the impact of the program.